A Perspective on the Emergence of Sialic Acids as Potent Determinants Affecting Leishmania Biology. (25th July 2011) - Ghoshal, Angana; Mandal, Chitra
Abstract : Leishmaniasis caused by Leishmania sp . has a wide range of manifestations from cutaneous to the deadly visceral form. They shuttle between the invertebrate and vertebrate hosts as promastigotes and amastigotes having adaptations for subverting host immune responses. Parasite-specific glycoconjugates have served as important determinants influencing parasite recognition, internalization, differentiation, multiplication, and virulence. Despite the steady progress in the field of parasite glycobiology, sialobiology has been a less traversed domain of research in leishmaniasis. The present paper focuses on identification, characterization, and differential distribution of sialoglycotope having the linkage-specific 9- O -acetylated sialic acid in promastigotes of different Leishmania sp . causing different clinical ramifications emphasizing possible role of these sialoglycotopes in infectivity, virulence, nitric oxide resistance, and host modulation in Leishmania spp . asserting them to be important molecules influencing parasite biology.